Perlindungan Hak Cipta Karya Sinematografi Melalui Digital Rights Management Pada Platform Over The Top - Ni Putu Esa Puja Laksmi; Putu Wahyu Widiartana (Warmadewa Press, 2025)
The rapid growth of the cinematographic industry in the digital era, particularly through Over The Top (OTT) platforms, has made it easier to distribute creative works to a wider audience while creating new challenges for copyright protection. Although copyright protection in Indonesia is legally regulated under Law Number 28 of 2014 and reinforced by the WIPO Copyright Treaty, piracy and illegal distribution of cinematographic works remain widespread. Previous studies have mostly focused on copyright protection in conventional media, while in-depth research on the role of Digital Rights Management (DRM) in the OTT ecosystem is still limited. This research aims to analyze how Indonesian law regulates the copyright protection of cinematographic works through DRM, and to evaluate the extent to which DRM implementation by OTT services aligns with national and international copyright protection principles. This study uses normative legal methods with statutory and conceptual approaches. The findings show that Indonesia’s legal framework for DRM is normatively adequate in safeguarding creators’ moral and economic rights, but its implementation faces challenges such as weak technical regulations, lack of supervision, and low awareness among local OTT industries. This research recommends developing more detailed implementing regulations, enhancing technical standards, and providing broader legal education to industry players, so that copyright protection in the era of digital distribution can be more effective, fair, and sustainable.